The Sultan's fleet - Isom-Verhaaren, Christine, 19??- (London)
viii sayfa, [6] sayfa harita, 275 sayfa
Keywords: “While the Ottoman Empire is most often recognized today as a land power, for four centuries the seas of the Eastern Mediterranean were dominated by the Ottoman Navy. Yet to date, little is known about the seafarers who made up the sultans' fleet, the men whose naval mastery ensured that an empire from North Africa to Black Sea expanded and was protected, allowing global trading networks to flourish in the face of piracy and the Sublime Porte's wars with the Italian city states and continental European powers. In this book, Christine Isom-Verhaaren provides a history of the major events and engagements of the navy, from its origins as the fleets of Anatolian Turkish beyliks to major turning points such as the Battle of Lepanto. But the book also puts together a picture of the structure of the Ottoman navy as an institution, revealing the personal stories of the North African corsairs and Greek sailors recruited as admirals. Rich in detail drawn from a variety of sources, the book provides a comprehensive account of the Ottoman Navy, the forgotten contingent in the empire's period of supremacy from the 14th century to the 18th century.” --